2022
DOI: 10.3390/jmse10060804
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Ship Trajectory Prediction Based on AIS Data Using MHA-BiGRU

Abstract: According to the statistics of water transportation accidents, collision accidents are on the rise as the shipping industry has expanded by leaps and bounds, and the water transportation environment has become more complex, which can result in grave consequences, such as casualties, environmental destruction, and even massive financial losses. In view of this situation, high-precision and real-time ship trajectory prediction based on AIS data can serve as a crucial foundation for vessel traffic services and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Although this approach is highly accurate, the complexity of the calculations is high and the results are influenced by the quality and size of the dataset. Bao (Bao et al, 2022) et al used the MHA-BiGRU method based on the multi-head self-attention mechanism and the bidirectional gated cyclic unit model, which was experimentally proved to be effective in reducing the error of trajectory prediction, but the quality requirements of the data were high, and the interpretability was poor, which was difficult to understand.…”
Section: Related Workmentioning
confidence: 99%
“…Although this approach is highly accurate, the complexity of the calculations is high and the results are influenced by the quality and size of the dataset. Bao (Bao et al, 2022) et al used the MHA-BiGRU method based on the multi-head self-attention mechanism and the bidirectional gated cyclic unit model, which was experimentally proved to be effective in reducing the error of trajectory prediction, but the quality requirements of the data were high, and the interpretability was poor, which was difficult to understand.…”
Section: Related Workmentioning
confidence: 99%
“…A point worth emphasizing is that in terms of time-series prediction, compared with using RNN and its variants alone, some research work has combined the RNN model prediction output with the attention mechanism in deep learning. These results show that the introduction of attention mechanism can improve the accuracy of timing prediction to a large extent [30][31][32]. The attention mechanism is a method for rapidly selecting high-value information from huge amounts of information.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, to pay more attention to important bidirectional temporal features so as to effectively improve the prediction performance, we add an attention mechanism to BiGRU. The attention mechanism adaptively calculates the weights for features, assigning greater weights to important features to allow them to play a larger role in prediction [17][18]. Recent studies have shown that adding attention mechanisms to models can significantly improve performance [19][20][21].…”
Section: Background Introductionmentioning
confidence: 99%